2004
DOI: 10.1021/jo049132r
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Palladium-Catalyzed Cross-Coupling of β-Chloroalkylidene/arylidene Malonates Using Microwave Chemistry

Abstract: A general method for the synthesis of beta-aryl/alkylarylidene malonates is reported. The key step involves the coupling of an arylboronic acid to a beta-chloroalkyl/arylidene malonate, in the presence of K2CO3 and 1 mol % of the air-stable palladium catalyst (POPd) under microwave irradiation, to afford beta-aryl/alkylarylidene malonates in good yields. The combination of mild reaction conditions, air stable catalyst, microwave-enhanced chemistry, and high levels of functional group compatibility make this an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The coupling of an arylboronic acid to a β-chloroalkyl/arylidene malonate in the presence of K2CO3 and 1 mol% of the air-stable palladium catalyst, [(t-Bu)2P(OH)]2PdCl2, under microwave irradiation affords β-aryl/alkylarylidene malonates, which were synthesized mainly upon Knoevenagel condensation. The mild reaction conditions allow a variety of arylboronic acids bearing electron-rich, electron-deficient, sterically demanding systems, amino and hydroxyl functionality to afford the products in good yields, Scheme 20 [54]. Schotten's group has reported that palladium acetate catalyzes the cross-coupling reaction of poly(ethylene glycol) (PEG) ester of bromo-, iodo-, and triflate-para-substituted benzoates with aryl boronic acids in water under microwave irradiation for 2-4 min (Scheme 19).…”
Section: Suzuki Cross-coupling Reactionmentioning
confidence: 99%
See 1 more Smart Citation
“…The coupling of an arylboronic acid to a β-chloroalkyl/arylidene malonate in the presence of K2CO3 and 1 mol% of the air-stable palladium catalyst, [(t-Bu)2P(OH)]2PdCl2, under microwave irradiation affords β-aryl/alkylarylidene malonates, which were synthesized mainly upon Knoevenagel condensation. The mild reaction conditions allow a variety of arylboronic acids bearing electron-rich, electron-deficient, sterically demanding systems, amino and hydroxyl functionality to afford the products in good yields, Scheme 20 [54]. Schotten's group has reported that palladium acetate catalyzes the cross-coupling reaction of poly(ethylene glycol) (PEG) ester of bromo-, iodo-, and triflate-para-substituted benzoates with aryl boronic acids in water under microwave irradiation for 2-4 min (Scheme 19).…”
Section: Suzuki Cross-coupling Reactionmentioning
confidence: 99%
“…The coupling of an arylboronic acid to a β-chloroalkyl/arylidene malonate in the presence of K2CO3 and 1 mol% of the air-stable palladium catalyst, [(t-Bu)2P(OH)]2PdCl2, under microwave irradiation affords β-aryl/alkylarylidene malonates, which were synthesized mainly upon Knoevenagel condensation. The mild reaction conditions allow a variety of arylboronic acids bearing electron-rich, electron-deficient, sterically demanding systems, amino and hydroxyl functionality to afford the products in good yields, Scheme 20 [54]. The coupling of an arylboronic acid to a β-chloroalkyl/arylidene malonate in the presence of K 2 CO 3 and 1 mol% of the air-stable palladium catalyst, [(t-Bu) 2 P(OH)] 2 PdCl 2 , under microwave irradiation affords β-aryl/alkylarylidene malonates, which were synthesized mainly upon Knoevenagel condensation.…”
Section: Suzuki Cross-coupling Reactionmentioning
confidence: 99%
“…The formation of 15-membered meta, meta-cyclophane, biphenomycin B have several biological activities, such as antimuscarinic activity, antibacterial activity, and antifungal activity 106, featuring a key microwave-induced intramolecular Suzuki-Miyaura reaction step, which was carried out by using controlled microwave heating to increase the cyclization efficiency in the key C-C coupling reaction of the tripeptide 105 precursor [90]. The best yield was obtained when using a toluene-water solvent system in the presence of TBAB (tetrabutylammonium bromide) as an additive (Scheme 35).…”
Section: Suzuki Coupling Reactionmentioning
confidence: 99%
“…2‐Methyl quinolone 2 a was prepared as outlined in Scheme through a Gould–Jacob procedure. The reaction of 3‐chloro‐4‐nitroaniline with diethyl 2‐(1‐chloroethylidene)malonate 13 8 gave intermediate 14 which, following cyclization with refluxing diphenylether, furnished the desired ethyl 7‐chloro‐2‐methyl‐6‐nitro‐4‐oxo‐1,4‐dihydroquinoline‐3‐carboxylate, along with 30 % of its regioisomer (ethyl 5‐chloro‐2‐methyl‐6‐nitro‐4‐oxo‐1,4‐dihydroquinoline‐3‐carboxylate). The mixture was difficult to separate and was, therefore, used directly in the successive methylation step to yield desired N ‐methyl derivative 15 following purification.…”
Section: Chemistrymentioning
confidence: 99%